Associations between lead concentrations and cardiovascular risk factors in U.S. adolescents - Cheng Xu (Nature Portfolio, 2017)
Abstract Little is known regarding the effects of environmental lead exposure on cardiovascular risk factors in the adolescent population. We studied 11,662 subjects included in the National Health and Nutrition Examination Survey (NHANES) 1999–2012. Blood lead levels were analysed for their association with cardiovascular risk factors (CVRF). Regression coefficients (Beta) and 95% confidence intervals (CIs) of blood lead in association with CVRF (e.g., total cholesterol, HDL-cholesterol, LDL-cholesterol, triglyceride, fasting glucose, glycohemoglobin, fasting insulin, and blood pressure) were estimated using multivariate and generalized linear regression after adjusting for age, gender, ethnicity, serum cotinine, body mass index (BMI), physical activity, and household income. We identified a strong positive association between blood lead (coefficient = 0.022, 95% CI 0.003, 0.041; P = 0.022) and LDL-cholesterol in adolescents (age 12–19 years). However, no associations with other CVRFs were found in the overall population. In the generalized linear models, participants with the highest lead levels demonstrated a 1.87% (95% CI 0.73%, 3.02%) greater increase in serum LDL-cholesterol (p for trend = 0.031) when compared to participants with the lowest lead levels. These results provide epidemiological evidence that low levels of blood lead are positively associated with LDL-cholesterol in the adolescent population.